Transgender stigma and health: A critical review of stigma determinants, mechanisms, and interventions. - White Hughto, Jaclyn M; Reisner, Sari L; Pachankis, John E (Social science & medicine (1982), 2015)
Transgender people in the United States experience widespread prejudice, discrimination, violence, and other forms of stigma.